Influence of individual and social values on customer engagement in luxury thermal spa hotels: The mediating roles of perceived justice and brand experience - Japutra, A.; Loureiro, S. M. C.; Molinillo, S.; Primanti, H. (Tourism and Hospitality Research, 2025)
This study aims to examine how values (i.e., individual and social values) influence customer engagement after managing a service failure in the thermal spa hotel context, and the mediating roles of perceived justice and brand experience. The data was collected from a survey of guests of luxury thermal spa hotels in Portugal, and the research model was assessed using partial least squares structural equation modeling. The results show that individual values affect perceived justice and brand experience, which in turn contribute to a higher level of customer engagement. Brand experience is a better mediator of the relationship between individual values and customer engagement than perceived justice. The novelty of this study is highlighted by the mediating effects of perceived justice and brand experience on the relationship between individual values and customer engagement.